MODEL PELAYANAN PEMBELAJARAN PENDIDIKAN INKLUSIF PADA SISWA BERKEBUTUHAN KHUSUS DI TENGAH PANDEMI COVID-19 - Maria Elviani Jelita; Maria R.I. Misales (Jurnal Pelayanan Pastoral, 2022)
During the COVID-19 pandemic, almost all education in Indonesia changed the learning system, including education for children with special needs. Children are required to study at home with parental assistance but still under the supervision of the teacher. The purpose of this study was to determine the model of learning services for children with special needs amid the covid-19 pandemic. This research uses the library method. The results showed that the distance learning service model applied was 5M learning. First Humanizing the relationship by building positive relationships between teachers, students and parents. Second, Understanding Concepts. Third, to build sustainability by reflecting with parents. Fourth, Choosing challenges by providing a variety of learning activities according to student conditions and flexible learning hours. Fifth, Empowering context. Based on the results of this study the use of the 5M distance learning strategy has contributed to teachers and parents in collaborating to educate students with special needs so that they can learn and remain productive during the pandemic covid-19.